HUKUM WARIS ADAT BATAK TOBA DITINJAU DARI KOMPILASI HUKUM ISLAM - Simarmata, Junior; Ashari, Ade Galih Putra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This paper discusses the customary inheritance law of the Batak Toba people in North Sumatra, Indonesia, in light of the Compilation of Islamic Law (KHI). The Batak Toba people are a patrilineal society with a strong emphasis on male primogeniture. This means that inheritance is passed down to the male heirs, with the eldest son receiving the largest share. The KHI, on the other hand, is a statutory compilation of Islamic law that applies to all Muslims in Indonesia. The KHI adopts a more egalitarian approach to inheritance, with both male and female heirs receiving shares of the estate. This paper examines the tensions between these two systems of inheritance law. It argues that the customary inheritance law of the Batak Toba people is discriminatory against women and violates the principles of Islamic law. The paper also discusses the challenges of reforming customary inheritance law in Indonesia. The paper begins by providing a brief overview of the customary inheritance law of the Batak Toba people. It then discusses the KHI's provisions on inheritance, with a focus on the rights of female heirs. The paper then examines the tensions between these two systems of law. It argues that the customary inheritance law of the Batak Toba people is discriminatory against women in a number of ways. First, it gives the eldest son a larger share of the estate than his siblings. Second, it excludes daughters from inheriting certain types of property, such as land. Third, it allows for the disinheritance of daughters in certain circumstances. The paper then argues that the customary inheritance law of the Batak Toba people violates the principles of Islamic law. The KHI states that all heirs, regardless of gender, are entitled to a share of the estate. The KHI also prohibits the disinheritance of heirs without a valid reason. The paper concludes by discussing the challenges of reforming customary inheritance law in Indonesia. It argues that reform must be carried out in a way that respects the cultural traditions of the Batak Toba people while also ensuring that women's rights are protected